Mode of delivery and outcomes among inborn extremely preterm singletons: A cohort study - Colm P. Travers; Dhuly Chowdhury; Abhik Das; Namasivayam Ambalavanan; Myriam Peralta‐Carcelen; Nancy Newman; Shirley Cosby; Myra Wyckoff; Alan Tita; Waldemar A. Carlo; For the Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Cesarean delivery is the most common mode of delivery among extremely preterm infants but there are insufficient data regarding the best mode of delivery among extremely preterm singletons. The objective of this study was to compare the rate of death or severe neurodevelopmental impairment among extremely preterm singletons by actual mode of delivery. Material and Methods Observational study using prospectively collected data from 25 US medical centers. We included postnatally‐treated singletons with birth weight 401–1000 g, gestational age 22 + 0/7–26 + 6/7 weeks, without a major birth defect, born 2006–2016. Death or severe neurodevelopmental impairment (Bayley Scales of Infant Development‐3rd edition cognitive composite score<70, cerebral palsy (Gross Motor Function Classification Scale >3), bilateral blindness, or bilateral hearing loss) at 18–26 month follow‐up were compared by mode of delivery (cesarean, vaginal including vertex or breech) using propensity score analysis to adjust for baseline characteristics. Results There was no difference in death or severe neurodevelopmental impairment between cesarean and vaginal (vertex or breech) births (42.4% cesarean vs. 47.2% vaginal; adjusted odds ratio (aOR), 95% confidence intervals (CI); 1.03, 0.91–1.17). Both cesarean delivery (26.8% cesarean vs. 51.5% breech vaginal; aOR: 0.71; 95% CI: 0.55–0.92) and vertex vaginal delivery (28.5% vertex vaginal vs. 51.5% breech vaginal; aOR: 0.59; 95% CI: 0.45–0.76) were associated with lower mortality compared with breech vaginal delivery. Conclusions Among postnatally‐treated extremely preterm singletons, there was no difference in death or severe neurodevelopmental impairment between cesarean or vaginal delivery. Both vertex vaginal and cesarean delivery were associated with lower mortality compared with breech vaginal delivery.